Fiscal policy in an endogenous growth model with horizontally differentiated intermediate goods - Ψαριανός Ιάκωβος Ν. (SPOUDAI Journal of Economics and Business, 2002)
Theoretical and empirical work in endogenous growth theory suggests that market economics underinvest in scientific and technical research and achieve growth rates that are lower than the socially optimal. Among the suggested explanations are the positive productivity spillovers associated with the nature of knowledge as a nonrival and only partially excludable good, the monopolistic pricing of the product of R&D, and the related issue of imperfect patent protection and imitation. This paper studies the above distortions in a model where technological progress is the product of research activity and takes the form of expansions in the variety of intermediate goods. The market and the socially optimal solutions are presented and the first-best fiscal policy is considered for each case of market failure. JEL Classification: H32,033, 038, O40, 041